Implementasi Data Mining Metode C.45 untuk Memprediksi Peminat Kuota Internet pada Masa Covid 19 - Susana, Heliyanti; Khofidoh, Shanti; Afghani, Azhar Al (MEANS (Media Informasi Analisa dan Sistem), 2022)
During the Covid 19 pandemic, Telering experienced an increase in sales and there were several internet SIM cards that consumers were less interested in. Various kinds of internet cards are sold and offered to attract consumers' attention, but it cannot be predicted which internet cards the consumers will be interested in. The C4.5 algorithm is a data classification algorithm with a decision tree technique that has advantages. These advantages, for example, can process numeric (continuous) and discrete data, can handle missing attribute values, produce easy rules. The results of the study explain that all providers including Telkomsel, Indosat, and axis are in demand by consumers. In analyzing using the C.45 algorithm with the Rapidminer Tools, the first is that the decision tree results in determining consumer interest are seen from the price, while the accuracy using the C.45 algorithm or decision tree produces an accuracy of 94.67%.